PENGARUH ELEMEN FRAUD TRIANGLE TERHADAP TINDAK KECURANGAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN BUMN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023) - Dewi Permatasari; Agus Sumanto (CV. Denasya Smart Publisher, 2025)
This study aims to examine the influence of the Fraud Triangle elements on the condition of financial statements. Specifically, this study examines the fraud triangle theory, which is represented by financial stability, industry characteristics, and total accruals to total assets This study uses M-Score Model to proxy the condition of financial statements. The study population consists of all non-financial state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Purposive sampling was applied as the sampling method, resulting in a total of 18 companies as the research sample. The data used secondary data. The data used are secondary data. A quantitative approach and logistic regression analysis were used in hypothesis testing with SPSS software. The results show that the rationalization variable has a positive effect on conditions in financial statements. Meanwhile, the financial stability and industry characteristics variables do not have a positive effect on financial statement conditions.